How are you peeling? : foods with moods - Freymann, Saxton; Elffers, Joost (New York : Arthur A. Levine Books, 1999)
Brief text and photographs of carvings made from vegetables introduce the world of emotions by presenting leading questions such as "Are you feeling angry?"
Keywords: Vegetable carving -- Juvenile literature; Emotions -- Juvenile literature; Emotions